Awe, tragedy and the human condition - Halstead, J. Mark (International journal of children's spirituality, 2004)
This article, reporting on research in progress on the nature of tragedy, falls into three sections. The first explores the concept of awe and relates it to contemporary thinking about spiritual education. The second identifies tragedy as an artistic form that evokes awe in response to the vision of the human condition that it presents. The theories of Aristotle and Nietzsche are examined in support of this view of tragedy. The third section looks at ways that tragedy can be taught in the classroom that allow space for students' emotional responses.